Culture intelligent workflow, structure, and steps - Henry, James Andrew (Frontiers in Artificial Intelligence, 2023)
Abstract Technologies abstract intelligence and provide predictor and precision insight in workflows that manage disorders, similar to cardiology and haematological disease. Positive perceptions of Artificial Intelligence (AI) that support Machine Learning (ML) and Deep Learning (DL) manage transformations with a safe system that improves well-being. In sections, workflow introduces an eXamination (X=AI) as an end-to-end structure to culture workstreams in a step-by-step design to manage populace health in a governed system. Method To better healthcare outcomes, communities and personnel benefit from an explanation and an interpretive that elucidates workflow for citizens or practitioners to comprehend personalised platforms. Therefore, the author undertook structure and practice reviews and appraised perspectives that impact the management of AI in public health and medicine. Results Figures for the management of AI workflow illustrate and inform on the model, structure, culture, assurance, process steps, values and governance required for abstract insights in public health and medicine. The papers’ end-to-end structure with explanans in a work culture interprets the step-by-step designs that manage the success of AI. Personalised care graphics offer an explanandum in the management of biological analytic value. Discussion Healthcare leadership collaboratives plan population health with an upstream, workplace and workstream format. Secure workflow and safety well-being system requirements prove that genomics and AI improve medicine. Therefore, the paper discusses group understanding of current practice, ethics, policy, and legality. Conclusion “Culture, intelligent workflow, structure, and steps” improve well-being with personalised care and align a percept for national opportunities, regional control, and local needs. Personalised practice cultures support analytic systems to describe, predict, precision, and prescript medicine in population health management eXaminations.